Freedom From The Traumatic Effect In Safe Haven Movie Script - Paruntu, Kezia Aviska; Wuntu, Ceisy N.; Mamentu, Agustine C. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2025)
This study explores the theme of freedom from traumatic effects as depicted in the film "Safe Haven," directed by Lasse Hallström and based on Nicholas Sparks' novel of the same name. The narrative follows the protagonist, Katie, who escapes an abusive marriage to find solace in a small coastal town. The study highlights Katie's psychological struggle with post-traumatic stress disorder (PTSD) resulting from her abusive past, emphasizing the impact of isolation, fear, and violence on her mental well-being. Through a qualitative analysis of the film's script, the research delves into Katie's journey towards healing, showcasing her efforts to build new relationships and establish a sense of safety in her life. Data collection includes main sources like the film itself and sources like books, papers, and the internet. The researcher uses a psychological approach to analyze the movie, focusing on the main character's battle for freedom. Ultimately, the film serves as a powerful testament to the resilience of survivors of domestic violence and the importance of love and support in overcoming trauma.